2016
DOI: 10.1063/1.4962009
|View full text |Cite
|
Sign up to set email alerts
|

Operation mechanism of high performance organic permeable base transistors with an insulated and perforated base electrode

Abstract: The organic permeable base transistor is a vertical transistor architecture that enables high performance while maintaining a simple low-resolution fabrication. It has been argued that the charge transport through the nano-sized openings of the central base electrode limits the performance. Here, we demonstrate by using 3D drift-diffusion simulations that this is not the case in the relevant operation range. At low current densities, the applied base potential controls the number of charges that can pass throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 22 publications
3
38
0
Order By: Relevance
“…[22] It can thus be assumed that any effects of on-stress predominantly occur in the base electrode region. At the base electrode an accumulation channel is formed and all charge carriers pass through nanometer-sized holes in the thin aluminum film.…”
Section: Electrical Stress Conditionsmentioning
confidence: 99%
“…[22] It can thus be assumed that any effects of on-stress predominantly occur in the base electrode region. At the base electrode an accumulation channel is formed and all charge carriers pass through nanometer-sized holes in the thin aluminum film.…”
Section: Electrical Stress Conditionsmentioning
confidence: 99%
“…The output characteristic in Fig. 1d shows a clear saturation behavior, although the channel length of this device is in the nm-range16. Typically, such short channel devices lose their saturation behavior due to short channel effects.…”
Section: Resultsmentioning
confidence: 90%
“…Simulations reveal that this happens exactly when charge carrier accumulation starts at the bottom of the base layer. [10] Hence, it can be concluded that the anodization at 2 V creates a very dense oxide layer on top of the base layer that successfully blocks all leakage current.…”
Section: Resultsmentioning
confidence: 97%
“…The base leakage current (10 -10 A) is decreased by about 4 orders of magnitude compared to a naturally oxidized base in previous reports, [9,17] with the leakage current being suppressed below the measurement limit for an anodization voltage of 4 V. With the base current being that low and decoupled from the collector and emitter currents, the OPBT can now be regarded as a field effect-transistor, as already proposed by simulations. [10] Although, the transmission is increased due to the anodization, the on-current of the transistor is reduced for higher anodizing voltage. This effect probably originates from a lower electric base-emitter field across the oxide in combination with a reduced number of pinholes (discussed later in the manuscript).…”
Section: Resultsmentioning
confidence: 99%